93 A CASE OF G-CSF(GRANULOCYTE-COLONY STIMULATING FACTOR) PRODUCING ESOPHAGEAL CANCER WITH ENTEROBLASTIC DIFFERENTIATION. (17th September 2021) - Kitamura, Yu; Oshikiri, Taro; Takiguchi, Gosuke; Urakawa, Naoki; Hasegawa, Hiroshi; Yamamoto, Masashi; Kanaji, Shingo; Matsuda, Yoshiko; Yamashita, Kimihiro; Matsuda, Takeru; Nakamura, Tetsu; Suzuki, Satoshi; et al.
Abstract:  : Granulocyte-colony stimulating factor (G-CSF) producing tumor is one type of growth factor producing tumor that induces leukocytosis. On the other hand, adenocarcinoma with enteroblastic differentiation disease is known as α-fetprotein (AFP), glypican3, and Sal-like protein 4 (SALL4) producing tumor. We report a first case of G-CSF producing esophageal cancer with enteroblastic differentiation which has never been reported in the world. Methods: [Case presentation]: A fifty-six year-old man was admitted to our hospital to treat esophageal carcinoma. His body temperature was elevated. Blood biochemistry tests showed leukocytosis (WBC 14000/μl). Gastroscopy revealed a 10-cm diameter, superficial elevated lesion in the lower thoracic esophagus. Biopsy findings indicated a diagnosis of adenocarcinoma. No distant metastasis, but right subclavian and para esophageal lymph nodes swelling were identified via computed tomography. Thus, we planned neo adjuvant chemotherapy (NAC) (5-FU 800 mg/m2 plus Cisplatin 80 mg/m2) before surgical resection. The patient's hyperthermia and leukocytosis improved by not antibiotics but NAC. Therefore, we suspected G-CSF producing tumor. Results: The serum level of G-CSF was markedly elevated at 133 pg/ml (normal range, <39 pg/ml). Additionally, PET/CT showed abnormally high uptake of (18) F-FDG not only by the tumor itself, but also diffusely throughout the bone marrow. The patient underwent minimally invasive esophagectomy in the prone position with two-field lymph node dissection. Immunohistochemical studies showed G-CSF producing adenocarcinoma with enteroblastic differentiation (AFP negative, glypican3 and SALL4 positive). Pathological stage was pT2N0M0, stageII. After resection, improvement of hyperthermia, leukocytosis, and serum level of G-CSF can be seen. Findings of (18) F-FDG throughout the bone marrow were also disappeared. Conclusion: We experienced an extremely rare case of G-CSF producing, esophageal adenocarcinoma with enteroblastic differentiation.